IMS 552: Information System Management. Group Assignment: Information Systems in National Archive of Malaysia / Ahmad Fakhrullah Adli … [et al.] - Adli, Ahmad Fakhrullah; Roslan, Muhammad Ridhwan; Jaafar, Muhammad Faeizwan; Mohd Sukor, Mohammad Norrashid (2015)
Information system is a tool, which facilitates a more universal view to be adopted by information systems consultants and developers. By this existing method, people will easy to collect data from many sources such as data mining, information retrieval, internet and cloud data management, web semantics, visual and audio information systems, scientific computing, and organizational behavior. For this project, we had chosen to study an information system that being use by our National Archive. The reason why we choose it is because we have been familiar with the system and understand about the Archive management so it would make us easier to understand the concept and explanations about the system. Moreover it also much easier for us to contact with the Archives compare to other organization. This may happen because of Archive always welcome people to visits their place as they themselves provide information to the public. While other organization may feel unsecured to share about their background and organization.